2022
DOI: 10.1186/s13071-022-05287-7
|View full text |Cite
|
Sign up to set email alerts
|

Protein profiling of hemolymph in Haemaphysalis flava ticks

Abstract: Background Tick hemolymph bathes internal organs, acts as an exchange medium for nutrients and cellular metabolites, and offers protection against pathogens. Hemolymph is abundant in proteins. However, there has been limited integrated protein analysis in tick hemolymph thus far. Moreover, there are difficulties in differentiating tick-derived proteins from the host source. The aim of this study was to profile the tick/host protein components in the hemolymph of Haemaphysalis flava. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 79 publications
0
13
0
Order By: Relevance
“…4). Hemolymph in engorged adult H. flava was discovered using liquid chromatography-tandem mass spectrometry (LC-MS/MS) in an earlier investigation (Liu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…4). Hemolymph in engorged adult H. flava was discovered using liquid chromatography-tandem mass spectrometry (LC-MS/MS) in an earlier investigation (Liu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Proteases and protease inhibitors are involved in many important processes to arthropod physiology such as development, reproduction, immunity, digestion, and even in vector-host interaction, as observed for salivary protease inhibitors found in some hematophagous species. , The presence of protease inhibitors has been described in the hemolymph of many other arthropod species where they were shown to be involved in regulating hemolymph clotting, immune responses, and antimicrobial defenses. ,,, , In A. aegypti, it has been already reported that bacterial challenges led to higher expression of different serpins .…”
Section: Resultsmentioning
confidence: 99%
“…By searching the UniProt Oryctolagus cuniculus database, we identified a total of 13 and 16 host proteins from RhHEEVs and HaHEEVs (Additional file 15 : Table S11), respectively. Among these, alpha-globin 1, hemoglobin, albumin, alpha-2-macroglobulin and histone H2A have been previously identified in tick saliva and hemolymph proteomics [ 52 , 53 ]. The presence of host-derived proteins suggests that tick hemolymph EVs may be involved in the transport of host proteins.…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with previous proteomic research on tick saliva [ 80 ]. However, Liu et al found that hemolymph collected from engorged Haemaphysalis flava was enriched with host proteins [ 53 ]. How these host proteins are transported from the midgut to the hemolymph is unclear.…”
Section: Discussionmentioning
confidence: 99%